In vitro and in vivo characterization of mutations in the human Indian hedgehog gene associated with brachydactyly type A1 and acrocapitofemoral dysplasia - Cunningham, Graeme (University of Ottawa (Canada), 2008)
Brachydactyly type A1 (BDA1) is a congenital disorder that affects normal bone development and patterning. Affected individuals have short fingers, broad hands and are generally short in stature. Acrocapitofemoral dysplasia (ACFD) is a chondrodysplasia characterized by variable short stature of the affected individual with short limbs, brachydactyly in the hands and feet, a relatively large head, and a narrow thorax with pectus deformities. Missense mutations in the Indian hedgehog (IHH) gene have been shown to be responsible for both disorders. We were the first group to successfully characterize the functional consequences of four BDA1-associated mutations (E95K, D100N, R128Q and E131K), and one ACFD-associated mutation (V190A). In stably transfected HEK293 cells, production and secretion of each mutant was significantly compared in comparison to the wild-type. When a LIGHT2 and a differentiating ATDC5 reporter cells were treated separately with normalized amounts of BDA1-associated mutant IHH-N, significantly reduced reporter activity in both cell lines was detected. Little increase in activity was noted when the reporter cells were treated with an equal combination of mutant and WT IHH-N, consistent with a dominant-negative effect. Furthermore, morpholino-induced 'knock-down' of zebrafish ihha revealed a crucial role for ihha in early zebrafish angiogenesis. Co-injection of human Ihh mRNA, although improving the phenotype, did not completely rescue it. Injection of mutant Ihh mRNA alone resulted in approximately 25% of the embryos displaying an altered phenotype - further evidence of a dominant negative effect. Ultimately, our in vitro and in vivo analysis led to the development of a likely model for the pathogenesis of both brachydactyly type A1 and acrocapitofemoral dysplasia.
Keywords: Biology, Molecular.; Chemistry, Biochemistry.